2017
DOI: 10.1177/0008417417701229
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and work discrimination among cancer survivors: A scoping review and recommendations

Abstract: Occupational therapists can enhance awareness of workplace concerns and advocate on behalf of cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 46 publications
3
26
1
Order By: Relevance
“…Admittedly, perceived personal discrimination is directly associated with a lower physical quality of life [47]. is can be explained by the myth that cancer is contagious and can always lead to death [48]. Univariate analysis of current work suggested that GHS/ QOL was positively associated with occupational status, which is consistent with previous studies [49,50].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Admittedly, perceived personal discrimination is directly associated with a lower physical quality of life [47]. is can be explained by the myth that cancer is contagious and can always lead to death [48]. Univariate analysis of current work suggested that GHS/ QOL was positively associated with occupational status, which is consistent with previous studies [49,50].…”
Section: Discussionsupporting
confidence: 81%
“…Admittedly, perceived personal discrimination is directly associated with a lower physical quality of life [ 47 ]. This can be explained by the myth that cancer is contagious and can always lead to death [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Everything became meaningless once they thought of death or the impossibility of recovery. This type of stigma would lead survivors to deny access to supports and limit their participation in social and work roles, thus solidifying negative perceptions about working after cancer 27,28 . This vicious cycle may enhance the risk of unemployment.…”
Section: Discussionmentioning
confidence: 99%
“…According to a nationwide survey in Korea, 44.7% of participants agreed that cancer patients had poor performance due to lack of concentration and memory loss 32 . Employees or coworkers may have negative misconception about cancer patients' work ability, which cause them to reassign job tasks or positions, or even exclude them from team projects 6,27,28 . Discrimination at the workplace might be more problematic for survivors whose jobs are less secure or those who work at small and medium enterprises, including those who are self‐employed 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation